BIBLIOTERAPI PADA NOVEL AYAT-AYAT CINTA DALAM MENINGKATKAN PENERIMAAN DIRI ISTERI YANG DIPOLIGAMI - Ifadatul Hasanah; Mohamat Hadori; Akhmad Zaini (Maddah : Jurnal Komunikasi dan Konseling Islam, 2020)
Bibliotherapy is a guideline in solutions to overcome personal problems through reading. While the novel is one of the print media that is read and can be used as a media preaching by a preacher in conveying a message to his honey. Through novel reading, it is hoped that polygamous wives can gain self-acceptance, especially in the first wife who experiences polygamy. And the results of the overall benchmark from the wife's self-acceptance questionnaire from cycle I and cycle II, provided an increase in score which was rather inflated from a total of 24 to 30. Ie from a score of 24 was occupying medium self-acceptance that can still be controlled by the counselee in dealing with the problems they face. And increasing the score to 30 is the level of self-acceptance at the first safe point